(3OjhGf GdTGYQ Gdeadbs - (3CMeO GdYfGjGJjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO abO bGd GdTjN CMeO Hf eMeO GdTgjQ HGdYfGjGJi MeOkG def Yde HGdbde hCXgQ GdaVd dfG cGdYde hejR GdEfSGf HGdHjGf eTQakG HGdbdH hGddSGf s
(3BNQgG (B:s
(3bO bVi bdHi HGdYTb Ydi bjS ai djdi hZjdGf Hei Ef HPd GdQhM ai TQY Gdghi gh TQW ddeMH GdYPQi JeJ GdOjhGf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B150s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs